Synthesis, characterization and photo catalytic degradation of aqueous eosin over Cr containing Ti/MCM-41 and SiO2-TiO2 catalysts using visible light - Awate, S. V.; Jacob, Nalini E.; Deshpande, Suvarna S.; Gaydhankar, T. R.; Belhekar, Anagha A. (Journal of Molecular Catalysis A - Chemical, 2005)
Two series of samples were prepared namely Cr-Ti/MCM-41 and Cr/SiO2-TiO2 keeping Si/Ti mole ratio same, with different Cr loading. The physico-chemical properties of the samples were characterized by different analytical techniques such as XRD, FTIR, TEM, low temperature N-2 sorption, and UV-vis diffused reflectance spectroscopy. The impregnated TiO2 was in anatase form. The crystallite size was determined from Scherrer equation as well as by TEM. There is a difference between the shapes of nitrogen adsorption isotherms with and without Cr-loaded Ti/MCM-41 samples. The rate of nitrogen adsorption was found to increase with decrease in Cr content at lower P/P-0 for Cr-Ti/MCM-41 samples due to the blocking of the pores with Cr. All MCM-41 samples exhibited pore sizes from 24 nm to 32 nm. UV-vis diffused reflectance spectra of all Cr-loaded samples showed red shift of their absorption edges. Photo degradation of eosin dye was studied using visible light. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Cr-Ti/MCM-41; Cr/SiO2-TiO2; eosin; photo degradation; visible light

Synthesis, characterization and photocatalytic behavior of TiO2-SiO2 mesoporous composites in hydrogen generation from water splitting - Niphadkar, P. S.; Chitale, S. K.; Sonar, S. K.; Deshpande, Suvarna S.; Joshi, P. N.; Awate, S. V. (Journal of Materials Science, 2014)
TiO2-SiO2 mesoporous composite photocatalysts with different proportions (in wt%) of TiO2 and SiO2 (TiO2-SiO2 = 20:80, 40:60, 60:40, 80:20 and 100:0) were prepared by loading TiO2 on as-synthesized Si-MCM-41 using sol-gel method. The physicochemical properties of composites were investigated by powder X-ray diffraction, N-2 adsorption-desorption measurements, transmission electron microscopy and UV-Vis diffuse reflectance spectroscopy. It is revealed that the titanium species are dispersed as TiO2 having interaction with the surface of the support. Even at high TiO2 loading, the mesostructural feature of MCM-41 was found to be intact without pore blockages. The change in morphology of TiO2 particle was observed with increase in TiO2 loading which may be due to different environment for the growth of TiO2. The photocatalytic evaluation of composites was carried out in production of hydrogen by water splitting. Among the prepared samples, mesoporous composite containing 60 % TiO2 (MTi60) has shown the best results (0.08805 mmol of H-2/h/g of TiO2) compared to other composite photocatalysts. The catalytic performance of this sample was further enhanced (similar to 8 times) after loading 1 % Pt in water splitting (0.70161 mmol of H-2/h/g of TiO2). 1 % Pt loaded on pure TiO2 (MTi100) showed hydrogen evolution of the magnitude 0.26 mmol of H-2/h/g of TiO2. TiO2-SiO2 mesoporous composite photocatalyst showed much higher activity (similar to 1.9 times) than amorphous silica-embedded titania catalyst having same composition.

Synthesis of Sn-containing anatase (TiO2) by sol-gel method and their performance in catalytic water splitting under visible light as a function of tin content - Tangale, N. P.; Niphadkar, P. S.; Samuel, V.; Deshpande, Suvarna S.; Joshi, P. N.; Awate, S. V. (Materials Letters, 2016)
Sol-gel route was employed to prepare a series of Sn-containing anatase with different molar (Ti/Sn) ratios ranging from 49 to 1. Samples were characterized by powder XRD, UV-vis, XPS, SEM, EDAX, low temperature N-2 sorption technique and Raman Spectroscopy. Except anatase phase, no other crystalline phase was observed when Ti/Sn molar ratio was varied from 49 to 9 and for Sn free sample. However, further decrease in the ratio lead to the appearance of additional SnO2 phase whose peak intensities were increased with the increase in the tin content. Irrespective of tin content, all samples showed red-shift in UV-vis spectra. Moreover, samples showed Raman shift to higher vibration side from 143 cm(-1) to 147 cm(-1) indicating the doping of Sn2+ into TiO2. By virtue of low band gap, anatase crystallite size and an absence of XRD visible SnO2, ST (19) has shown maximum photocatalytic activity upon 1 wt% Pt loading. It has exhibited the highest rate (0.1264 mmole/g/h) for visible light induced hydrogen evolution by water splitting. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Semiconductors; Sn2+ doped titania; SnO2/TiO2; Sol-gel preparation; visible light; water splitting